Effect of root-associated bacteria on corn nitrogen use efficiency - Squizani de Arruda, Wagner (My University, 2024)
Nitrogen (N) is a critical input for corn (Zea mays L.) production, essential for optimizing crop growth and yield. However, a significant portion of synthetic N fertilizers is lost to the environment, leading to negative ecological impacts, such as groundwater contamination and greenhouse gas emissions. Optimizing nitrogen management is, therefore, crucial for sustainable agricultural production. This study evaluated the bacterial inoculant Proven®, which colonizes corn roots with nitrogen-fixing bacteria, potentially enhancing nitrogen use efficiency (NUE), biomass accumulation, and grain yield. The experiment employed a split-plot randomized complete block design for over three years (2021-2023) at the Agronomy North Farm, Manhattan, KS. The main plot treatments consisted of four nitrogen rates (0, 56, 112, and 168 kg N ha⁻¹) applied as urea, while Proven®, applied in-furrow at planting, served as the subplot treatment, with six replicates. Plant biomass and nitrogen uptake were measured at the vegetative eight-leaf (V8), tasseling (VT), and maturity (R6) growth stages, with grain yield and NUE metrics calculated at R6. Proven® demonstrated a stage-specific effect on dry matter accumulation and nitrogen uptake, particularly at the V8 and VT stages, when treated plants showed increased dry matter and enhanced nitrogen uptake compared to untreated plants. Despite these improvements, the overall effect on grain yield and NUE indices was limited, with no significant differences observed across the three years. Proven®-treated plants exhibited greater nitrogen uptake at earlier growth stages, but this did not consistently translate into improved NUE metrics. While the production metrics were not significantly enhanced, the use of Proven® offers potential environmental benefits by facilitating biological nitrogen fixation. This could reduce reliance on synthetic fertilizers, decrease nitrogen losses, and mitigate environmental issues such as groundwater contamination and greenhouse gas emissions. These findings suggest that while Proven®'s effectiveness may vary depending on environmental conditions and growth stages, its role in promoting sustainable agriculture and reducing the ecological footprint of nitrogen fertilization warrants further investigation, with attention to factors such as climate and soil variables to optimize its application.
Keywords: Biological Nitrogen Fixation (BNF); Bioinoculant; N-fixing bacteria in corn; Nitrogen Use Efficiency (NUE)